Kebermanfaatan Penggunaan Geogebra dalam Pembelajaran Matematika - Joko Purnomo (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2021)
The use of Information and Communication Technologies (ICT) in a variety of educational activities creates lots of conveniences, increases effectiveness and efficiency. It is believed that the use of ICT in the educational process makes learning more interesting, enables explaining the concept more clearly, foster creativity, collaborative skills and many more. Due to the fact that the students are millennial generation, who is quite familiar with ICT in their daily life, the use of ICT is important. In learning mathematics, GeoGebra which is dynamic open source software can be used as a teaching and learning tool for mathematics. However, some are still unaware of the benefits of using GeoGebra to learn mathematics. This article discusses the various benefits of using GeoGebra in mathematics teaching and learning, and several studies that support it. The advantages of using GeoGebra in mathematics teaching and learning are as follows: GeoGebra might be used to demonstrate or visualize mathematical concepts, as well as a means of constructing mathematical concepts. The use of GeoGebra in mathematics learning can foster mathematical reasoning, creativity, support collaboration, involve students more in the learning process. And, the more involved, more effective and efficient the learning is.